Acts of Unlawful Interference As the Main Threat To the Russian Federation Transport Security - Nikita S. Riazanov (Сибирское юридическое обозрение, 2017)
Separate threats to the Russian Federation transport security are considered, an analysis of the concept, features and essence of «an act of unlawful interference» category is given. The ways of improvement of legislation in the field of study are proposed.